PENDAMPINGAN PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN DENGAN MENGINTEGRASIKAN KEGIATAN BERTANI BERSAMA ORANG TUA PADA GURU RAUDHATUL ATHFAL (RA) IGRA di SUKOREJO PASURUAN - Mamilianti, Wenny; Swasono, Muh. Aniar Hari; S.Ag., MA, Wiwin Wiwin Fachrudin Yusuf (Universitas Mataram, 2024)
IGRA Sukorejo, which is an organization of Raudhatul Athfal (RA) teachers in Sukorejo District, has implemented a program of learning and playing with parents in farming and processing the results of farming. The initial idea for learning to farm with family was to foster togetherness with parents while fulfilling children's nutrition. This IGRA plan has not been implemented optimally due to limited resources, such as human resources and supporting facilities and infrastructure, in addition, the Learning Implementation Plan has not been integrated into the curriculum. The purpose of this activity is to improve teachers' ability in preparing a Learning Implementation Plan on Farming with Parents as a local content subject in Raudhatul Athfal (RA). The PKM implementation approach method used is Socialization, Training/workshop, Mentoring, Monitoring and Evaluation. The result of this activity was an increase in the skills of Raudhatul Athfal (RA) teachers, 86.67% or 26 people were able to prepare and complete RPP. The post-test results showed that out of 30 participants representing 15 RAs at IGRA Sukorejo, they stated that they were willing to implement the science and technology provided in RA student learning. This activity provides new knowledge and skills for RA teachers in preparing the implementation of agriculture-based learning. The increase in teachers' knowledge and skills in preparing lesson plans is proven by the availability of agricultural lesson plans that are ready to be implemented.